2017
DOI: 10.1080/10717544.2017.1375576
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the transport and absorption of Angelica sinensis polysaccharide through gastrointestinal tract both in vitro and in vivo

Abstract: To investigate the absorption and delivery of ASP in gastrointestinal (GI) tract, cASP was successfully synthesized by chemically modifying with succinic anhydride and then conjugating with a near infrared fluorescent dye Cy5.5. Then, the capacity of oral absorption of cASP was evaluated. The results demonstrated that cASP had low toxicity and no disruption on the integrity of cell membrane. The endocytosis of cASP into the epithelial cells was time- and energy-dependent, which was mediated by macropinocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 61 publications
(80 reference statements)
1
38
0
Order By: Relevance
“…lucidum, a Chinese medicinal mushroom, has been widely used in the treatment of chronic hepatopathy with little or no side effects of various etiologies [15]. It could be absorbed into the epithelial cells after oral administration through endocytosis process mainly mediated by macropinocytosis pathway and clathrin -and caveolae (or lipid raft) -related routes and then be absorbed and circulated into blood [16]. Polysaccharide in G. lucidum (GLPS) has been proposed as the bioactive constituents responsible for the protective activities against toxin-induced liver injury [15].…”
Section: Introductionmentioning
confidence: 99%
“…lucidum, a Chinese medicinal mushroom, has been widely used in the treatment of chronic hepatopathy with little or no side effects of various etiologies [15]. It could be absorbed into the epithelial cells after oral administration through endocytosis process mainly mediated by macropinocytosis pathway and clathrin -and caveolae (or lipid raft) -related routes and then be absorbed and circulated into blood [16]. Polysaccharide in G. lucidum (GLPS) has been proposed as the bioactive constituents responsible for the protective activities against toxin-induced liver injury [15].…”
Section: Introductionmentioning
confidence: 99%
“…The human colon carcinoma cell line, Caco-2 could slowly differentiate to form a cell monolayer that possesses many functions of the small intestinal villus epithelium. Caco-2 cell monolayer has been widely used in the early screening of drug development and had become an important model to study the mechanism of drug absorption and transport [24]. The above results showed that LBP had no significant effect on the viability of Caco-2 cells, but it could be internalized into Caco-2 cells and partially locate in lysosomes ( Figure S11), suggesting no toxicity of LBP to Caco-2 cells.…”
Section: Transport Of Dye Labeled Lbp Through Caco-2 Cell Monolayermentioning
confidence: 88%
“…Due to the large molecular mass and high hydrophilicity of polysaccharides, it is difficult to enter cells by passive diffusion [39]. Some studies have shown that clathrin mediates the internalization process of polysaccharides [24]. The clathrin-dependent pathway includes three key steps: cell membrane infolding that depends on clathrin, vesicle formation that relies on dynamin, and endosome maturation.…”
Section: The Uptake Of Dye Labeled Lbp By Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations